Comparison of Sling Suspension Versus Balance and Proprioceptive Exercise for Patients with Knee Osteoarthritis - Vivi Mariani; Lanny Indriastuti (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Objectives: To compare the difference between sling suspension versus balance and proprioceptive exercise’s effect on pain and functional capacity of knee osteoarthritis patients before, 2 weeks after and 4 weeks after exercise.Methods: This longitudinal study with case series design was done on 34 subjects with knee osteoarthritis grade II and III in Outpatient Clinic of Medical Rehabilitation Installation in Dr. Kariadi General Hospital Semarang from November 2009 to February 2010. They were randomly assigned into ‘sling suspension’ and ‘balance and proprioceptive’ exercise group. Each group contains 17 subjects. Subjects conducted their exercise 3 times a week for four weeks. Assesment of VAS, WOMAC modification index, TUG test were done before, 2 weeks after and 4 weeks after exercise.Results: There were statistically significant changes in pain (measured by VAS category) and functional capacity (measured by WOMAC modification index subscale of pain, stiffness and functional activity, and TUG test) before, 2 weeks after and 4 weeks after exercise in both groups (p<0.05). However, there were no statistically significant difference in pain and functional capacity between groups (p>0.05).Conclusions:There were no significant diffrences between sling suspension and balance and proprioceptive exercise, although both exercise gave significant improvement in vas category, WOMAC modification index and walking time on TUG test.Keywords: knee osteoarthritis, sling suspension exercise, balance and proprioceptive exercise, VAS,